Intron RNA editing is essential for splicing in plant mitochondria - Castandet, Benoît (Oxford University Press, 2010)
Most plant mitochondria messenger RNAs (mRNAs) undergo editing through C-to-U conversions located mainly in exon sequences. However, some RNA editing events are found in non-coding regions at critical positions in the predicted secondary and tertiary structures of introns, suggesting that RNA editing could be important for splicing. Here, we studied the relationships between editing and splicing of the mRNA encoding the ribosomal protein S10 (rps10), which has a group II intron and five editing sites. Two of them, C2 and C3, predicted to stabilize the folded structure of the intron necessary for splicing, were studied by using rps10 mutants introduced into isolated potato mitochondria by electroporation. While mutations of C2 involved in EBS2/IBS2 interactions did not affect splicing, probably by the presence of an alternative EBS2′ region in domain I of the intron, the edition of site C3 turned out to be critical for rps10 mRNA splicing; only the edited (U) form of the transcript was processed. Interestingly, RNA editing was strongly reduced in transcripts from two different intronless genes, rps10 from potato and cox2 from wheat, suggesting that efficient RNA processing may require a close interaction of factors engaged in different maturation processes. This is the first report linking editing and splicing in conditions close to the in vivo situation.